PEMBANGUNAN PARTISIPASI POLITIK DALAM PILKADA : MENUJU PEMERINTAHAN DAERAH YANG DEMOKRATIS - Yuliandari, Erna (PKn Progresif, 2007)
The election of local executive is a phenomena local event. Discourse about this phenomenon that direct election would bring good governance in local level. There is a proposition that derives from theoretical generalization of prosedural democracy and political recruitment need direct elections of local leader to bring the sovereignty back to the people; So it needs a recruitment process that reflect an active and optimal participation of the people, and to guarantee the contestations of candidates. Afterwards will emerge a leader that comform to the people?s preference. Participation of the people need to anticipate the growing of democratization not only to be a procedura. Democracy but a substantive Democracy.